Analisis Pajak Daerah dan Inflasi terhadap Belanja Daerah dengan Pertumbuhan Ekonomi sebagai Variabel Moderasi di Provinsi Sumatra Barat - Pramita, Pramita; Putra, Gerry Hamdani (Lembaga Yasin AlSys, 2026)
Although the relationship among local taxes, inflation, and regional expenditure has been widely discussed in previous studies, research examining the role of economic growth as a moderating variable in this relationship remains limited, particularly in local governments in West Sumatra Province. This study aims to analyze the effect of local taxes and inflation on regional expenditure, with economic growth as a moderating variable in West Sumatra Province. This study used a quantitative approach with secondary data obtained from the Central Statistics Agency (BPS) and relevant government agencies. The research sample covered regencies and cities in West Sumatra Province during the 2020–2024 period. The data were analyzed using descriptive statistics, classical assumption tests, hypothesis testing, and Moderated Regression Analysis (MRA). The results showed that local taxes had a positive and significant effect on regional expenditure, whereas inflation had no significant effect on regional expenditure. In addition, economic growth was not proven to strengthen the relationship between local taxes and regional expenditure or the relationship between inflation and regional expenditure. These findings support fiscal decentralization theory, which emphasizes the importance of regional fiscal capacity in supporting development and public services. Thus, this study contributes to the development of the literature on regional finance and macroeconomics, particularly regarding the interaction between fiscal and economic variables in local government management. The practical implications of this study emphasize the importance of formulating fiscal policies, controlling inflation, and managing regional expenditure more effectively to support sustainable economic development in West Sumatra Province.